Weather and electrical demand and consumption data of a small Mexican community - Milagros Santos-Moreno; Jorge Ángel González-Ordiano; J. Emilio Quiroz-Ibarra; D.A. Perez-DeLaMora; Jaime Mizrahi-Cojab; Emilio Román-Sánchez; José Pablo Montero-Cantú; Lazaro Bustio-Martinez (Data in Brief, 2024)
The development of novel technologies to mitigate the effects of climate change through Smart Grids requires energy related data. Unfortunately, this type of data is not always available in Mexico, especially from non-large urban areas and at the household level. Therefore, we present a dataset that contains electrical demand and consumption time series of 5 households within a small community in Mexico, at various resolutions, as well as weather data. The electrical demand is given in 15 min resolution, while the electrical consumption is presented in both hourly and daily resolutions. The data is contained within 15 separate .csv files; one for each household's resolution. In turn, the weather data is given in two .csv files (for outdoor and indoor variables, respectively) that together contain 24 meteorological variables measured in a 5 min resolution that is not always consistent. The dataset comprises of two separate folders that contain either the electrical demand and consumption files or the weather files. This dataset could aid in the development of novel smart grid methods and algorithms that might be able to push the energy transition in Mexico and other developing countries forward.